Socio-economic determinants of Dairy Farmers’ Knowledge on Dairy Farming Practices in Uttar Pradesh, India - Saurabh Sharma; Herojit Singh; Sabbithi Pavan (Journal of Extension Education, 2024)
The study was carried out among dairy farmers of Balamau block of Hardoi district of Uttar Pradesh to assess the socio-economic landscape and dairy farming practices. Utilizing a multistage purposive cum random sampling approach, data from 60 dairy farmers were collected and analyzed. Findings revealed diverse socio-economic backgrounds and educational levels among farmers, influencing their farming decisions. Buffalo predominated the livestock, with significant variations in milk production of cross breeds. Reproductive parameters underscored opportunities for improvement. Correlation and regression analyses elucidated education, training participation, social participation and scientific orientation as pivotal predictors of knowledge level in dairy management. Higher education and greater participation in training sessions were associated with better management practices. The study emphasizes the significance of education, continuous learning and scientific orientation in optimizing dairy farming practices and enhancing industry profitability offering valuable insights for stakeholders in the field. Regression analysis explained 62.10% of knowledge variation, emphasizing education, family type, training, social participation, and scientific orientation.